Ailing, Aging, Addicted : Studies of Compromised Leadership - Park, Bert Edward (Book collections on Project MUSE., 1993)
What role did drug abuse play in John F. Kennedy's White House, and how was it kept from the public? How did general anesthetics and aging affect the presidency of Ronald Reagan? Why did Winston Churchill become more egocentric, Woodrow Wilson more self- righteous, and Josef Stalin more paranoid as they aged -- and how did those qualities alter the course of history?Was Napoleon poisoned with arsenic or did underlying disease account for his decline at the peak of his power? Does syphilis really explain Henry VIII's midlife transformation? Was there more than messianism brewing in the brains o.